Adoption of Articles 6 and 7 of the Rome Statute of 1998 on Genocide and Crimes Against Humanity in Law Number 26 of 2000 on Human Rights Courts - Eva Arief; Novia Mungawanah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Serious human rights violations that occur in Indonesia, such as in Aceh, Papua, Jakarta, Poso and East Timor, fall into the category of crimes against humanity. Indonesia adopted the principles of international law into national law, which were adapted to the ideological values of the Indonesian nation, namely Pancasila, namely adopting the principles of genocide (mass extermination of an ethnic group) and the principles of crimes against humanity contained in Article 6 and 7 Rome Statute 1998. Partially the Rome Statute was implemented in national law by adopting it through Law Number 26 of 2000 concerning Human Rights Court. The problem that arises is how the provisions of Article 6 and 7 of the 1998 Rome Statute concerning genocide and crimes against humanity were adopted in Law Number 26 of 2000 concerning the Human Rights Court. This research uses a normative juridical approach by studying or analyzing secondary data in the form of secondary legal materials by understanding law as rules or norms which are benchmarks for human behavior that is considered appropriate. Research using this normative juridical method essentially emphasizes the deductive method as a general guide, and inductive method as support. Article 6 of the 1998 Rome Statute concerning Genocide (Mass Extermination of an ethnicity) and Article 7 of the 1998 Rome Statute concerning Crime Against Humanity are included in the group of serious human rights violations. Indonesia has an interest in promulgating Law Number 26 of 2000 driven by the desire to fulfill the complementary principles adopted by the 1998 Rome Statute so that Law Number 26 of 2000 concerning trials for serious human rights violations meets the minimum standarts international law. The 1998 Rome Statute is an international agreement that cannot be reserved so that ratification of the 1998 Rome Statute is fully binding of ratifying countries so that the Indonesian government must be careful in ratifyng it, but for Indonesia's interests, several principles and provisions in the 1998 Rome Statute were adopted.